THE SADNESS OF EPARCHIUS AVITUS (SIDONIUS, CARM. 7.519-21). (26th October 2016) - Green, Roger
Abstract : In his panegyric of Avitus, his father-in-law, the poet Sidonius gives a vivid and often detailed picture of the career of the future emperor from his boyhood until he gained the supreme power in the West in the year 455, which he owed to his ability and accomplishments in warfare, diplomacy and administration. He also enjoyed strong support from both Goths and Gauls, and his repeated success in managing the volatility and the aspirations of the Goths is a major theme. This short note seeks to contribute to the understanding of his emergence as Augustus by proposing a new interpretation of a pivotal passage (lines 519–24), quoted below. The context can be briefly given. Sidonius has painted a graphic picture of the reaction among the Goths to the news of the Vandal capture of Rome in the year 455 (lines 441–57). In the ensuing assembly of Gothic elders Avitus (who happens to be with them at Toulouse at this moment) gives a speech that vigorously praises peace (lines 458–86), and this is favourably received. There follows a speech from the Gothic king, Theoderic II, in which he puts his own strong case for an agreement between Goths and Gauls, and seeks to persuade Avitus to fill the vacuum in Rome and Italy caused by the recent death of the emperor Petronius Maximus and take the name of Augustus (lines 489–518).